Periodic Solutions of a Stage-Structured Plant-Hare Model with Toxin-Determined Functional Responses - Huicheng Wang; Patricia J. Y. Wong; Yonghui Xia (Abstract and Applied Analysis)
The purpose of this paper is to obtain some sufficient conditions for the global existence of multiple positive periodic solutions of a delayed stage-structured plant-hare model with a toxin-determined functional response. Some novel estimation techniques to construct two open subsets for a priori bounds are employed.